Characterization of an injectable, degradable polymer for mechanical stabilization of mandibular fractures. Issue 3 (17th June 2014) - Henslee, Allan M.; Yoon, Diana M.; Lu, Benjamin Y.; Yu, Joseph; Arango, Andrew A.; Marruffo, Liann P.; Seng, Luke; Anver, Tamir D.; Ather, Hunaiza; Nair, Manitha B.; Piper, Sean O.; Demian, Nagi; et al.
Abstract: This study investigated the use of injectable poly(propylene fumarate) (PPF) formulations for mandibular fracture stabilization applications. A full factorial design with main effects analysis was employed to evaluate the effects of the PPF: N ‐vinyl pyrrolidone (NVP, crosslinking agent) ratio and dimethyl toluidine (DMT, accelerator) concentration on key physicochemical properties including setting time, maximum temperature, mechanical properties, sol fraction, and swelling ratio. Additionally, the effects of formulation crosslinking time on the mechanical and swelling properties were investigated. The results showed that increasing the PPF:NVP ratio from 3:1 to 4:1 or decreasing the DMT concentration from 0.05 to 0.01 v/w % significantly decreased all mechanical properties as well as significantly increased the sol fraction and swelling ratio. Also, increasing the crosslinking time at 37°C from 1 to 7 days significantly increased all mechanical properties and decreased both the sol fraction and swelling ratio. This study further showed that the flexural stiffness of ex vivo stabilized rabbit mandibles increased from 1.7 ± 0.3 N/mm with a traditional mini‐plate fixator to 14.5 ± 4.1 N/mm for the 4:1 (0.05 v/w % DMT) PPF formulation at day 1. Overall, the formulations tested in this study were found to have properties suitable for potential further consideration in mandibular fracture fixation applications. © 2014 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 103B: 529–538, 2015.